2010
DOI: 10.1603/ec09408
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Development and Emergence Pattern of <I>Hypothenemus hampei</I> (Coleoptera: Curculionidae: Scolytinae) From Coffee Berries

Abstract: The coffee berry borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae), is the most important constrain for coffee production throughout the world. Knowledge on the emergence pattern of H. hampei females to infest new berries is crucial to effectively plan control measures. In this laboratory study, we assessed the development of immature stages and the emergence pattern of H. hampei females from the berries by exposing them to temperatures that are typical for high-altitude plantations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 16 publications
3
31
0
4
Order By: Relevance
“…Life history traits such as high reproductive rate and short life cycle (Jaramillo et al, 2009) may account for the success of H. hampei as a devastating pest of coffee. Another factor is that H. hampei spends most of its life cycle inside the coffee berry that makes damage difficult to detect at first sight, and chemical spraying usually inefficient (Brun et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Life history traits such as high reproductive rate and short life cycle (Jaramillo et al, 2009) may account for the success of H. hampei as a devastating pest of coffee. Another factor is that H. hampei spends most of its life cycle inside the coffee berry that makes damage difficult to detect at first sight, and chemical spraying usually inefficient (Brun et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Since the beetle's life cycle is completed for several generations inside the bean, it is difficult to control this pest with pesticides or detect it with outside inspections. Although the beetle has been shown not to thrive in dry green bean or parchment (Trujillo, 1991;Jaramillo, 2010), observations have been made of live beetles in dry coffee beans after weeks of storage. Therefore, the Hawaii Department of Agriculture has established a quarantine regulation of the movement of coffee in any form to prevent introduction and spread of the pest within the state of Hawaii.…”
mentioning
confidence: 99%
“…Hypothenemus hampei (Ferrari; Coleoptera: Curculionidae; Scolytidae) is an important pest causing devastation of Coffee plantations in the sub-Saharan agricultural regions, especially in East Africa (Jaramillo, 2012;Jaramillo, Chabi-Olaye, & Borgemeister, 2010). Population flare-ups are exacerbated by increasing trends in temperatures and solar exposures (Jonsson, Ijala, Ekbom, Kyamanywa, & Karungi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jonsson et al (2014) working in the area reported a 17 per cent increase in growth rate of H. hampei per degree increase in temperature. There is evidence of changing thermal temperature trends due to global changes and anthropogenic influences, which create micro conditions at specific locations (Jaramillo et al, 2010(Jaramillo et al, , 2011(Jaramillo et al, , 2013Jason et al, 2005;Seymoure, 2018).…”
Section: Introductionmentioning
confidence: 99%